The rise of corporate compliance programs as a strategy against corruption: unpacking legal reforms in the Global South and North - Viol, Dalila Martins (2024)
Just over a decade ago, anti-corruption corporate compliance programs were a topic of interest only in a limited number of countries and, currently, they are commonplace around the world. Although scholars and policymakers have highlighted the dissemination of these programs, they have not systematically studied the rise of legal developments promoting them. More broadly, there is a dearth of literature on comparative anti-corruption legal strategies, with the few existing studies focusing on a limited number of jurisdictions from the Global North. This thesis is the first study to map and analyze the legal developments that promote compliance programs, in jurisdictions both in the Global South and in the Global North, underscoring a wave of legal reforms in this regard, notably during the 2010s. Despite relative convergence in the promotion of compliance programs, this study reveals significant local variation in the design of the legal strategies. This thesis develops a taxonomy of these strategies and reflects on the potential implementation challenges and consequences of established category. It also explores the promotion of compliance programs within the International Anti-Corruption Regime (IACR), indicating that while the IACR played a central role in promoting the punishment of corporate corruption globally, it did not exert the same influence on the dissemination of the legal incentive for compliance programs. This thesis contributes to the field of compliance program studies as a new area within comparative and international law scholarship, as well as to the growing understanding of the development of anti-corruption strategies around the world, especially in the Global South.